Wide voltage gain range application for full‐bridge LLC resonant converter with narrow switching frequency range. Issue 15 (1st October 2020) - Wei, Yuqi; Luo, Quanming; Wang, Zhiqing; Mantooth, Alan
Abstract : In wide voltage range applications, traditional LLC converters suffer from the following issues: (i) to cover a wide voltage gain operating range, the required switching frequency range is also large, which challenges the design and optimisation of magnetic components, gate driver circuitry, and electro‐magnetic interference filter; (ii) a small magnetising inductance is preferred in wide voltage gain range application, which leads to the increase of circuit circulating current and corresponding conduction loss; (iii) passive elements are determined based on the minimum switching frequency, so bulky passive elements are required to satisfy the required operation range. To solve these problems, in this study, a full‐bridge LLC (FBLLC) resonant converter with two operation modes, namely full‐bridge operation and frequency doubler operation, is proposed for wide voltage gain range application. The FBLLC converter discussed in this study can be designed in half of the input voltage range when compared with the conventional method, so smaller switching frequency operating range and higher efficiency operation are guaranteed. In addition, the smooth mode transition is achieved by introducing switching frequency feedforward control and small output voltage overshoot or undershoot is observed. A 150 W experimental prototype was built to validate the theoretical analysis.